Biology of Parasitoid Aganaspis daci (Weld) (Hymenoptera: Eucoilidae): Biology of A. daci - Andleeb, Saiqa; Shahid, Muhammad Shafiq; Mehmood, Riaz (Biological Sciences - PJSIR, 2010)
In view of the importance of Aganaspis daci (Trybliographa daci) and Diachaishmimorpha longicaudata parasitoids in the use of fruit fly control, biology of A. daci was studied under controlled temperature and humidity conditions. A. daci was found to be more dominant and easy to use as a biological control agent than the D. longicaudata.